Determinants of in-hospital feeding practices in Shiraz, Iran: Results of a prospective cohort study - Zarshenas, M.; Zhao, Yun; Binns, C.; Scott, J. (Wiley-Blackwell Publishing, 2018)
Background: In-hospital feeding practices have been shown negatively to affect breastfeeding exclusivity and duration. The purpose of this study was to report the prevalence and determinants of delayed breastfeeding, provision of traditional prelacteal foods, and use of infant formula in hospital. Methods: Between June 2014 and March 2015, 700 women were recruited from three public and two private maternity hospitals in Shiraz, Iran. Data were collected at recruitment via face-to-face interviews and extracted from medical records. Multivariable logistic regression was used to explore the association of feeding practices with a variety of maternal characteristics and hospital practices. Results: Only 32.2% of infants were breastfed within 1 hour of birth, with 40.8% receiving a traditional prelacteal food, and 34.9% given formula during their hospital stay. Compared with infants delivered vaginally, those delivered by cesarean were more likely to have experienced delayed breastfeeding and received formula, but less likely to have received traditional prelacteal foods. Infants who did not experience skin-to-skin contact were more likely to have experienced delayed breastfeeding and received traditional prelacteal foods and formula in hospital. Conclusions: Although four out of the five hospitals were designated as Baby-Friendly, several of the 10 Steps to Successful Breastfeeding were not adhered to. The high rate of cesarean delivery was a barrier to the early initiation of breastfeeding and the majority of infants did not experience early skin-to-skin contact. Maternity care practices should be reviewed and include a clear breastfeeding care plan for women who undergo a cesarean delivery.